2018
DOI: 10.3390/nu10121928
|View full text |Cite
|
Sign up to set email alerts
|

Water Intake, Water Balance, and the Elusive Daily Water Requirement

Abstract: Water is essential for metabolism, substrate transport across membranes, cellular homeostasis, temperature regulation, and circulatory function. Although nutritional and physiological research teams and professional organizations have described the daily total water intakes (TWI, L/24h) and Adequate Intakes (AI) of children, women, and men, there is no widespread consensus regarding the human water requirements of different demographic groups. These requirements remain undefined because of the dynamic complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 132 publications
(170 reference statements)
3
129
0
13
Order By: Relevance
“…They found better voice quality after adequate surface hydration. 16 Adequate hydration of the body is considered to be 2 liters or eight glasses of water 17,18 and agents that dehydrate the body result in decreased laryngeal hydration and thick secretions, which may block the ductal system of seromucinous glands with a resultant formation of a mucous retention cyst. We considered laryngeal hydration to be poor when a person consumed less than or equal to four glasses of water a day or consumed more than 8 caffeinated beverages (tea/coffee/cola) in a day.…”
Section: Discussionmentioning
confidence: 99%
“…They found better voice quality after adequate surface hydration. 16 Adequate hydration of the body is considered to be 2 liters or eight glasses of water 17,18 and agents that dehydrate the body result in decreased laryngeal hydration and thick secretions, which may block the ductal system of seromucinous glands with a resultant formation of a mucous retention cyst. We considered laryngeal hydration to be poor when a person consumed less than or equal to four glasses of water a day or consumed more than 8 caffeinated beverages (tea/coffee/cola) in a day.…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers stabilize within 24 hours to reflect the current water intake state. The mechanism behind changes in urine concentration and urine volume are due to changes in vasopressin, or anti‐diuretic hormone vasopressin, secretion which is released in response to body water excesses or deficits (Armstrong & Johnson, ). Biomarkers of urine concentration respond acutely to changes in water intake, unlike plasma osmolality, which is less responsive to acute changes in water intake (Cheuvront et al, ; Perrier et al, ).…”
Section: Assessing Individual‐level Hydration and Water Needsmentioning
confidence: 99%
“…Like other ELISA kits, it necessitates a full wet lab with microplate readers, an incubator, microtiter plate, graduated cylinders, distilled water, pipettes, and test tubes. While vasopressin is a newer biomarker of hydration, it is well correlated with urinary biomarkers of hydration and parlays into the neural circuitry designed to keep body water homeostasis (Armstrong & Johnson, ). However, vasopressin can be quite unstable in lab analyses, attaches to platelets and is cleared rapidly (Morgenthaler, Struck, Alonso, & Bergmann, ).…”
Section: Assessing Individual‐level Hydration and Water Needsmentioning
confidence: 99%
“…However, a recent randomized control study among those who already had stage 3 CKD found that those who received coaching to drink more water (an extra liter a day) did not have significantly slower declines in kidney function (Clark et al, ). Therefore, daily water intake among those without kidney damage likely provides the most benefits to kidney health (Armstrong & Johnson, ; Clark et al, ).…”
Section: Population Variation In Human Water Needsmentioning
confidence: 99%
“…Since water balance is intimately tied to health and physiological functioning, several systems exist, including thirst, to return the body to homeostasis (Oka, Ye, & Zuker, ). The body and brain detect water deficits and excesses thereby releasing or restricting the anti‐diuretic hormone vasopressin and conserving body water or excreting it with the signals getting stronger depending on the level of imbalance (Armstrong & Johnson, ).…”
Section: Introductionmentioning
confidence: 99%